2017
DOI: 10.1186/s12985-017-0852-z
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Newcastle disease virus rL-RVG enhances the apoptosis and inhibits the migration of A549 lung adenocarcinoma cells via regulating alpha 7 nicotinic acetylcholine receptors in vitro

Abstract: BackgroundThe aim of this study were to investigate the possible pro-apoptotic mechanisms of the recombinant Newcastle disease virus (NDV) strain rL-RVG, which expresses the rabies virus glycoprotein, in A549 lung adenocarcinoma cells via the regulation of alpha 7 nicotinic acetylcholine receptors (α7 nAChRs) and to analyze the relationships between α7 nAChR expression in lung cancer and the clinical pathological features.Methodsα7 nAChR expression in A549, LΑ795, and small-cell lung carcinoma (SCLC) cells, am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 39 publications
0
14
0
1
Order By: Relevance
“…According to the literature data, the selective antagonist of nAChR methyllycaconitine at high concentrations (1 to 10 µM) inhibits the proliferation of the A549 cells. However, this effect is relatively small and manifests itself predominantly after 48 and 72 h of incubation [42]. Considering much lower affinity of acylcholines for nAChR, as compared with methyllycaconitine, their cytotoxicity might not arise solely from the nAChR inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…According to the literature data, the selective antagonist of nAChR methyllycaconitine at high concentrations (1 to 10 µM) inhibits the proliferation of the A549 cells. However, this effect is relatively small and manifests itself predominantly after 48 and 72 h of incubation [42]. Considering much lower affinity of acylcholines for nAChR, as compared with methyllycaconitine, their cytotoxicity might not arise solely from the nAChR inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…The apoptosis level of SW1116 and SW480 cell transfection with RPN2 siRNA or control siRNA was assessed by flow cytometric assay. The overall cell apoptosis detection procedures were similar to the previously described procedures with slight modification on the cell numbers ( 23 ). In brief, the cells were washed and detached in 2 ml PBS with 2 mM ethylenediaminetetraacetic acid (EDTA) and centrifuged at 15,000 × g for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…The rL-RVG, NDV, anti-RVG antibody and anti-NDV antibody were stored at − 80°C supplied by the Harbin Veterinary Research Institute (Harbin, China). The human gastric cancer cell lines SGC7901 and BGC were purchased from the Cancer Cell Repository (Shanghai Cell Bank,2016- [11][12][13][14][15][16][17][18][19][20] and the American Type Culture Collection (Manassas,VA,USA). The cell line has been authenticated by STR (short tandem repeats, STR) and has been tested for mycoplasma contamination (Additional file 1).…”
Section: Methodsmentioning
confidence: 99%
“…Alpha 7-nAChR may be a potential therapeutic key point for the treatment of stomach cancer. Previous studies have also demonstrated that the recombinant avirulent NDV LaSota strain, expressing the rabies virus glycoprotein (rL-RVG), could induce the apoptosis of gastric cancer cells as well as suppress the migration of lung cancer cells by regulating α7-nAChR [13,14]. However, it still remains unclear whether rL-RVG could also suppress the migration of gastric cancer and its underlying mechanisms.…”
Section: Introductionmentioning
confidence: 99%